2009
DOI: 10.2353/ajpath.2009.090182
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded DNA Activates Glomerular Endothelial Cells and Enhances Albumin Permeability via a Toll-Like Receptor-Independent Cytosolic DNA Recognition Pathway

Abstract: Viral DNA induces potent antiviral immunity by activating dendritic cells; however, the mechanism governing viral DNA-mediated triggering or aggravation of glomerulonephritis is unknown. Glomerular endothelial cells (GEnCs) do not express toll-like receptor (TLR)9, the only DNA-specific TLR. We therefore hypothesized that DNA could activate GEnCs via the recently discovered TLR-independent viral DNA recognition pathway. Indeed, double-stranded non-CpG (B-) DNA activated GEnCs to produce interleukin-6, CCL5/RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 45 publications
(56 reference statements)
3
31
1
Order By: Relevance
“…Finally, we found that STING and CpG-ODN overlapped in NK cells. This result is consistent with the observation by Hagele et al (33) that DNA oligonucleotides present in endosomes may reach the cytoplasm. The existence of STING as an alternative cytosolic sensor for bacterial DNA may be an advantage for the detection of intracytoplasmic bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, we found that STING and CpG-ODN overlapped in NK cells. This result is consistent with the observation by Hagele et al (33) that DNA oligonucleotides present in endosomes may reach the cytoplasm. The existence of STING as an alternative cytosolic sensor for bacterial DNA may be an advantage for the detection of intracytoplasmic bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…From measured vessel diameters and centerline blood flow velocity, apparent wall shear stress was calculated, assuming a parabolic flow velocity profile over the vessel cross section. 51 As a measure of microvascular permeability, five postcapillary vessel segments as well as the surrounding perivascular tissue were excited at 488 nm, and emission .515 nm was recorded by a CCD camera (Sensicam, PCO, Kelheim, Germany) 30 minutes after injection of FITC-dextran (Sigma Aldrich) using an appropriate emission filter (LP 515). Mean gray values of fluorescence intensity were measured by digital image analysis (TILLvisION 4.0, TILL Photonics) in six randomly selected regions of interest (50350 mm 2 ), localized approximately 50 mm distant from the venule under investigation.…”
Section: In Vivo Microscopy On Mouse Cremaster Musclesmentioning
confidence: 99%
“…The transwell permeability of FITC-conjugated albumin in GEnC monolayer was performed as described. 50 Reactive oxygen species production in cultured GEnCs was determined using the electron spin resonance method. In brief, confluent GEnCs were stimulated with Cat-S with or without inhibitors in serum-free RPMI media.…”
Section: In Vitro Studiesmentioning
confidence: 99%